TOA estimation of UWB backscattering RFID tag with dual pulse modulation for clutter suppression - Xu, Chi (2013)
To realize precise localization for UWB backscattering RFID system, the arrival time of the direct path in the received signal (referred as time of arrival (TOA)) needs to be accurately estimated. The background clutter is one of the major factors that deteriorates the TOA estimation accuracy in backscattering RFID system. To suppress the background clutter while maintain low-complexity system design, we propose a novel UWB backscattering RFID system with its tag being implemented with dual pulse (DP) modulation. By transforming the mathematical model of received signal into a proper form, we discover the tag's sequence selection criteria which are able to mitigate the background clutter. For the proposed tag coded with dedicated sequences, a two-stage TOA estimation algorithm able to effectively mitigate clutter is developed. Simulation results show that the proposed RFID system coupled with the algorithm is able to achieve accurate TOA estimation in the environment where the clutter overwhelms the tag response.